Sources of health inequality for Irish women - David Madden (University College Dublin, Department of Economics, 2002)
This paper calculates the concentration index for self-assessed health for a sample of Irish women. It then decomposes the index to investigate the sources of this inequality using both a health production function and reduced form approach. Using the health production function approach it finds that age, employment status and exercise regime make the greatest contribution to income-related inequality in health outcomes. Using the reduced form approach it finds the greatest contribution to be made by age and education.
hdl:10197/775
Keywords: I12; 330; Inequality; concentration index; decomposition; health production function; Gesundheit; Frauen; Irland